Novel active driven drop tower facility for microgravity experiments investigating production technologies on the example of substrate-free additive manufacturing. Issue 8 (15th April 2018) - Lotz, Christoph; Wessarges, Yvonne; Hermsdorf, Jörg; Ertmer, Wolfgang; Overmeyer, Ludger
Highlights: Population of space requires new production processes. Einstein-Elevator: A unique facility for micro- and hypogravity research on earth. Additive manufacturing can be performed in space substrate-free. Abstract: Through the striving of humanity into space, new production processes and technologies for the use under microgravity will be essential in the future. Production of objects in space demands for new processes, like additive manufacturing. This paper presents the concept and the realization for a new machine to investigate microgravity production processes on earth. The machine is based on linear long stator drives and a vacuum chamber carrying up to 1000 kg. For the first time high repetition rate and associated low experimental costs can provide basic research. The paper also introduces the substrate-free additive manufacturing as a future research topic and one of our primary application.